2018
DOI: 10.3390/lubricants6020035
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Emulsification in Calibrating Infrared Spectroscopes for Analyzing Water Contamination in Used or In-Service Engine Oil

Abstract: Using Fourier transform infrared (FT-IR) spectroscopy we investigated the water content of SAE 15W-40 diesel engine lubricating oil at various levels of contamination to establish instrument calibration standards for measuring water contamination in used or in-service engine oil by the standards of ASTM International. Since some known additives in consumer grade engine oil possess slightly hydrophilic properties, this experiment avoided changing the sample matrix with supplemental additives, such as adding sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…Nevertheless, the concentration at which the moisture can be comfortably detected, in another words the limit of quanti cation (LOQ), is suggested at 1000 ppm. is recommendation is in line with the literature ndings where Dong et al [3] propose the LOD at 500 ppm whilst Holland et al [19] postulate at 1000 ppm, agreeing with Fitch [20]. In terms of precision, it is found that the prediction is subjected to high variance, indicative of unstable models.…”
Section: Resultssupporting
confidence: 86%
“…Nevertheless, the concentration at which the moisture can be comfortably detected, in another words the limit of quanti cation (LOQ), is suggested at 1000 ppm. is recommendation is in line with the literature ndings where Dong et al [3] propose the LOD at 500 ppm whilst Holland et al [19] postulate at 1000 ppm, agreeing with Fitch [20]. In terms of precision, it is found that the prediction is subjected to high variance, indicative of unstable models.…”
Section: Resultssupporting
confidence: 86%
“…In most of the recent studies, different traditional technologies, such as gas chromatography method [3], evaporation and distillation [4], near infrared spectrum [5], and voltammetric electronic tongue [6], are used to detect the quality of oil. Although these technologies are very precise, they are complicated to operate and consume a large amount of sample [7].…”
Section: Introductionmentioning
confidence: 99%
“…As NMR devices decrease in cost and size, they may become more prevalent for this purpose. However, current industry practices show that FT-IR use is still quite commonplace in this area, and prior research has indicated a need for more specific guidelines, including within the ASTM International standard of practice for using FT-IR [6], in order to maximize emulsions in water contaminated oil samples, particularly when preparing samples for IR calibration [7].…”
Section: Introductionmentioning
confidence: 99%
“…Instituting calibration standards for FT-IR analysis must begin with a thorough emulsification procedure, to establish an accurate baseline with which to compare an instrument's capabilities of detecting water in oil. A thoroughly emulsified sample is inherently more stable, homogeneous, and representative of the whole, yielding better reproducibility and reliability in results by reducing the variability in IR measurements that arises due to light scattering in samples with larger water droplet sizes [7,10]. Water contamination in used or in-service oil primarily exists in dissolved or emulsified states due to agitation, heat, and pressure caused by oil circulation through an engine.…”
Section: Introductionmentioning
confidence: 99%